Design Of Wideband Microstrip Bandpass Filter For S-Band Application - Salleh, Azahari; Mohamad, Najmiah Radiah; Hashim, Nik Mohd Zarifie; Abd Aziz, Mohamad Zoinol Abidin; Misran, Mohamad Harris (AENSI Publisher, 2014)
-